Rumination syndrome: pathophysiology, diagnosis, and treatment. Issue 4 (20th October 2016) - Absah, I.; Rishi, A.; Talley, N. J.; Katzka, D.; Halland, M.
Abstract: Background: Rumination syndrome is a functional gastrointestinal disorder characterized by effortless and repetitive regurgitation of recently ingested food from the stomach to the oral cavity followed by either re‐swallowing or spitting. Rumination is thought to occur due to a reversal of the esophagogastric pressure gradient. This is achieved by a coordinated abdominothoracic maneuver consisting of a thoracic suction, crural diaphragm relaxation and an increase in intragastric pressure. Careful history is important in the diagnosis of rumination syndrome; patients often report "vomiting" or "reflux" and the diagnosis can therefore be missed. Objective testing is available with high resolution manometry or gastroduodenal manometry. Increase in intra‐gastric pressure followed by regurgitation is the most important characteristic to distinguish rumination from other disorders such as gastroesophageal reflux. The mainstay of the treatment of rumination syndrome is behavioral therapy via diaphragmatic breathing in addition to patient education and reassurance. Purpose: The purpose of this review was to critically appraise recent key developments in the pathophysiology, diagnosis and therapy for rumination syndrome. A literature search using OVID (Wolters Kluwer Health, New York, NY, USA) to examine the MEDLINE database its inception until May 2016 was performed using the search terms "rumination syndrome, " "biofeedback therapy, " and "regurgitation." References lists and personal libraries of the authors were used to identify supplemental information. Articles published in English were reviewed in full text. English abstracts were reviewed for all other languages. Priority was given to evidence obtained from randomized controlled trials when possible. Abstract : This review critically appraises recent studies of pathophysiology and therapy for rumination syndrome.